Pengaruh Layanan Penguasaan Konten dan Teknik Token Ekonomi Terhadap Pembentukan Perilaku Asertif Siswa Kelas VIII SMP Negeri 1 Hiliduho - Elly (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
The implementation of guidance and counseling services for BK teachers is expected to be able to provide services according to its stages. The purpose of this study is to reveal the partial significant influence of content mastery services on the formation of assertive behavior, to reveal the partial significant influence of token economy techniques on the formation of assertive behavior, to reveal the joint influence of content mastery services with economy techniques on the formation of assertive behavior. Based on the results of the study in the form of instrument products, it can be confirmed that Content Mastery services (X1) with Token Economy (X2) on Student Assertive Behavior (Y), and every increase in Variable X1 with X2 will be followed by an increase of 1% will be followed by an increase in variable Y of 0.846%. This proves that Content Mastery services with Token Economy Techniques that are well organized are very effective in improving assertive behavior.